The virtual fracture clinic improves quality of care for patients with hand and wrist injuries: an assessment of 3709 patients. (September 2020) - Little, Max; Huntley, Daniel; Morris, James; Jozsa, Felix; Hardman, John; Anakwe, Raymond E.
Fracture clinic services are under significant pressures to meet patients' expectations of a high-quality service. The virtual fracture clinic has shown early promise in helping to reduce such pressures. We used the virtual fracture clinic for hand and wrist injuries treated in the orthopaedic fracture clinic and used key quality indicators to measure improvement. Over the first 21 months, key patient outcome measures and satisfaction scores for patients discharged from the virtual fracture clinic with education to self-care were excellent. Our results show that a virtual fracture clinic model can be applied to provide high-quality care for hand and wrist injuries. The main advantage of the virtual fracture clinic is its ability to direct patients to the right person for timely treatment. We conclude from our 21-month experience that this model of care allows safe, effective, patient-centred, efficient and equitable care to the patients with hand and wrist fractures. Level of evidence: IV